Facet, Junction and Electric Field Engineering of Bismuth‐Based Materials for Photocatalysis. Issue 20 (8th August 2018) - Li, Min; Huang, Hongwei; Yu, Shixin; Tian, Na; Zhang, Yihe
Abstract: Semiconductor photocatalysis has gained tremendous attention with great prospects to settle the worldwide environmental pollution and energy shortage issues. Many efforts have been made for semiconductor photocatalysts to overcome the disadvantages of the weak photoabsorption and high recombination of charges in the past few decades. Developing active facets and junctions has been diffusely used and shows huge potentials. The surface of active facet where the reductive and oxidative reactions occur has a great influence on the efficiency of reaction molecules that takes over the photogenerated charges. Construction of junctions is regarded as one of the most effective methods to improve the separation efficiency of photogenerated charges. This review mainly focuses on summarizing the synthesis of active facet, facet dependent activities in various photocatalytic reactions, the construction of different kinds of heterojunctions and homojunctions, and the combination of active facet and junctions of bismuth‐based photocatalysts recently. In addition, other new and effective routes, like internal electric field (IEF) regulation and polarization electric field control are also shortly summarized. The review will deepen our understanding on bismuth‐based photocatalysts and provide novel guidelines and perspectives for designing high‐performance photocatalysts. Abstract : Fascinating facets ! Here bismuth‐based photocatalysts are viewed with focusing on the synthesis of active facets, facet‐dependent activities in various photocatalytic reactions, the construction of different kinds of heterojunctions and homojunctions, the combination of active facets and junctions, internal electric field regulation and polarization electric field control of bismuth‐based photocatalysts.